Reorganizing the finance function – The employees’ perspectives on tasks, roles and identity after a shared services project - Hanski, Katri (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Especially during difficult financial times and in an environment of internationalization and intense competition, organizations need to think about being cost effective and gaining competitive advantage over others. The shared services center model and the outsourcing of finance functions have been an emerging trend during recent decades due to these changes. A lot of research has been done on the topic of shared services center projects but many areas have received only limited attention. The purpose of this study is to add to the current literature of the finance function by analyzing the shared services center models advantages, challenges and the change process from the point of view of the individual. With regard to the ideas of identity theories, this study takes the point of view of the employees that remain in the case organization in order to find out how they feel about the reorganization. The tasks, roles and identities of the employees are analyzed in the interest of finding out how their work and their roles have changed after the reorganization and what their perceptions are related to the change process. This study is a qualitative case study carried out by interviews in the case organization, the University of Turku. The findings of this study mostly support existing literature as the results indicate similar advantages and risks as previous studies. However, it can be concluded that while the tasks of the employees change due to the shared services project, it is still unclear whether their roles and identities change as well. Nevertheless, the study’s contributions to the current literature include insights into the perspectives of the employees and their views related to the shared services center project. As the individual point of view of shared services projects has received only limited attention in previous studies, this study adds to the existing literature by studying the experiences of the employees of the finance function related to their task, role and identity changes. In addition, this study contributes by providing insight into the advantages and risks of the shared services project from the point of view of the employees of the case organization.